2015
DOI: 10.1161/strokeaha.115.009861
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria, but Not eGFR, Predicts Stroke Risk in Chronic Kidney Disease

Abstract: Background and Purpose Chronic kidney disease (CKD) is associated with an increased risk of cardiovascular events. However, the impact of CKD on cerebrovascular disease is less well understood. We hypothesized that renal function severity would be predictive of stroke risk, independent of other vascular risk factors. Methods The study population included 3939 subjects enrolled in the Chronic Renal Insufficiency Cohort (CRIC) study, a prospective observational cohort. Stroke events were reported by participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 41 publications
(37 reference statements)
5
51
1
2
Order By: Relevance
“…These findings are similar to previous studies. Recently, reports from the Kailuan study and the Chronic Renal Insufficiency Cohort (CRIC) study both showed that proteinuria but not reduced eGFR increased the risk of stroke in a general and CKD population, respectively . The JATOS study demonstrated that baseline reduced eGFR per se (<60 versus ≥60 mL/min per 1.73 m 2 ) was not significantly associated with cardiovascular events ( P =0.1723); however, the presence of proteinuria was significantly correlated with cardiovascular event rates ( P =0.0001), an association that was more apparent in patients with an eGFR <60 mL/min per 1.73 m 2 ( P <0.0001) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to previous studies. Recently, reports from the Kailuan study and the Chronic Renal Insufficiency Cohort (CRIC) study both showed that proteinuria but not reduced eGFR increased the risk of stroke in a general and CKD population, respectively . The JATOS study demonstrated that baseline reduced eGFR per se (<60 versus ≥60 mL/min per 1.73 m 2 ) was not significantly associated with cardiovascular events ( P =0.1723); however, the presence of proteinuria was significantly correlated with cardiovascular event rates ( P =0.0001), an association that was more apparent in patients with an eGFR <60 mL/min per 1.73 m 2 ( P <0.0001) .…”
Section: Discussionmentioning
confidence: 99%
“…[2829] Furthermore, the Chronic Renal Insufficiency Cohort study recently reported that compared to eGFR, albuminuria is a better predictor of stroke risk in patients with CKD. [30]…”
Section: Discussionmentioning
confidence: 99%
“…First, the levels of proteinuria are likely to be randomly distributed in both arms, and thus of similar magnitude at baseline. Second, we do not expect the SPS3 population to have a high prevalence of severe proteinuria because participants had a relatively low prevalence of diabetes and, unlike CRIC 2 , SPS3 was not enriched for kidney disease. In addition, the use of inhibitors of the renin angiotensin system (ACE/ARB) was very high in both groups throughout the study.…”
mentioning
confidence: 99%